ANALISIS PERBEDAAN KINERJA PERUSAHAAN PADA SEKTOR PERBANKAN SEBELUM DAN SEMASA COVID-19 - Dea Aprilia Damayanti; Vera Puji Lestari; Nadia Elvita Sari; Eddy Suranta (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
This study aims to determine whether there are differences in company performance in the banking sector consisting of Earning Per Share (EPS), Return on Assets (ROA), Return on Equity (ROE), Net Interest Margin (NIM), and Operational Costs and Operating Income. . This study uses signal theory. The population and sample used in this study are banking companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period with several pre-existing sample criteria with 50 observations with a total of 25 companies. The method used is the Independent Sample t Test method. From the results of this study it is known that Earning Per Share (EPS), Return on Assets (ROA), and Operational Costs and Operating Income do not significantly influence company performance while Return onEquity (ROE), and Net Interest Margin (NIM) has a significant effect on company performance